Las metodologías ágiles y su relación con la gestión eficiente de proyectos - Briceño Agurto, Angela Maria (2024)
Organizations are continually searching for new ways to manage their projects efficiently, in order to be more competitive in the market. For this reason, this paper aimed to determine the relationship between agile methodologies and project management efficiency. The methodology used is correlational and cross-sectional, with a non-experimental design. The sample consisted of 139 developers of information technology projects from banking entities. The data was collected through two surveys; one of them measured the agility of the projects and the second measured the effectiveness of project management. Each questionnaire had 20 items on a Likert-type scale. The resulting value was 0.858 for the Spearman’s Rho coefficient, which demonstrates that there is a relationship between the implementation of an agile methodology and efficient project management. The relationship between the dimensions of customer collaboration, functional deliverables, response to change, and individuals and interactions with efficient project management was also demonstrated. This allows us to conclude that properly implementing an agile method increases the probability of successfully completing a project. However, it is necessary to have a trained work team to carry out the implementation, in addition to having the necessary resources to support management; all of this will allow the organization to achieve the desired results.